In vitro model improves the prediction of soil arsenic bioavailability: worst-case scenario - Quazi, Shahida; Nagar, Rachana; Sarkar, Dibyendu; Datta, Rupali K.; Sylvia, Victor L.; Makris, Konstantinos C. (My University, 2008)
There is a strong interest in developing an in vitro arsenic (As) model that satisfactorily estimates the variability in in vivo relative oral bioavailability (RBA) measurements. Several in vitro tests have been developed, but none is universally accepted due to their limited success in predicting soil As RBA. A suite of amorphous and crystalline solid As phases were chosen, utilizing a worst-case scenario (VVCS) that simulated fasting children's gastric solution chemistry. The objectives of this study were to (i) determine the effects of residence time, pH, and solid-to-solution ratio on As bioaccessibility and speciation in the in vitro gastric test; (ii) provide the fundamental basis for an optimized in vitro model constrained by the WCS; and (iii) validate the optimized in vitro test with the in vivo RBA obtained with BALB/c mice. The gastric pH was the only significant (p < 0.05) factor influencing solid As bioaccessibility. Bioaccessible As retained the oxidation state after its release from the solid into the gastric solution. The optimized in vitro model adequately predicted RBA values for a suite of solid As phases typically encountered in soils, with the exception of aluminum-based solids. This study is an excellent starting point for developing an in vitro test applicable to different As-contaminated soils.
Keywords: Arsenic bioavailability; BALB/c mice; Bioaccessibility; Bioaccessible; Contaminated soils; Crystalline solids; In vitro modeling; In vitro testing; In-vitro; In-vivo; Oral bioavailability; Oxidation states; Residence time; Solution chemistry; Solution ratio; Worst-case scenario